The Use of Mobile Learning in Higher Education: A Study on the MOOC of Cadi Ayyad University - Idrissi Jouicha, Abdellah; Burgos, Daniel; Berrada, Khalid (Lecture Notes in Networks and Systems, 2023)
With the rapid growth of mobile technologies, the evolution of mobile devices, and the progress in wireless communications and networking technologies, mobile devices have become very popular and have reached a very high spread. Consequently, mobile learning (m-learning) has become a prominent phenomenon and has revolutionized the entire education system. This paper aims to highlight the significant importance of mobile devices in the field of e-learning in higher education. To do so, we have conducted a study on a massive open online course (MOOC) created and implemented specifically to respond and blend into overcrowded classrooms and Amphitheaters. The obtained results showed that the integration and the use of m-learning facilitated the learners’ access to the teaching resources and materials offered by the University, and its promoted academic learning in classrooms and amphitheaters, in order to enhance the learning outcomes of the learners.
Keywords: blended learning; digital transformation; e-learning; educational innovation; educational technology; m-learning; MOOC; open education; Scopus(2)